LEGAL BASIS FOR THE ESTABLISHMENT OF THE SYSTEM OF TECHNICAL REGULATION ON RAILWAY TRANSPORT - Cherkashyn, Yu. M.; Khatskilevych, O. O.; Fedorova, D. V.; Yakovleva, E. V. (Science and Transport Progress, 2006)
Legal frameworks of creation of the system of the technical adjusting on a railway transport are considered in the article.